Prarancangan Pabrik 1-Hexana Dari Etilen Menggunakan Proses Alphahexol Dengan Disain Alat Utama Reaktor Oligomerisasi - Priska Tantino; Padil Padil (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
1-Hexene is a raw material in plastic production and classified as a linear alpha olefin compound. This compound is used as a co-monomer in the production of polyethylene, manufacture of lubricants, manufacture of surfactants and alcohol. The use of 1-hexene in the production of High-density polyethylene (HDPE) and linear low-density polyethylene (LLDPE) is one of the co-monomers. The need for 1-hexana in Indonesia is increasing over time, but in Indonesia there is no factory that produces 1-hexene. Therefore, the need for 1hexene has increased significantly in 2018. The increasing need for imports will reduce the source of foreign exchange for the country. So that the establishment of the 1-hexene plant can reduce the need for imports and can increase the country's foreign exchange. The location of the 1-hexana factory is planned to be in the RU II Dumai industrial area with a factory capacity of 100,000 tons / year. The main design is an oligomerization reactor (R101) which functions to react ethylene by trimerizing to 1-hexene with a 1-octene as a byproduct. The type of reactor used is a stirred tank flow reactor. The operating conditions in the reactor were 423.15 K and 30 bar. Plant economic analysis is carried out to determine the feasibility of the factory to be built. Based on the results of the economic feasibility analysis of the factory, the 1-hexana plant is feasible to build with a PBB of 2 years, an IRR of 22.7433%, an ROI of 39.388%, and a BEP of 54%.  Keywords: 1-Hexene,  Alphahexol, Analysis economic feasibility of plant, Ethylene.